2005
DOI: 10.1596/1813-9450-3571
|View full text |Cite
|
Sign up to set email alerts
|

Does tariff liberalization increase wage inequality ? - Some empirical evidence

Abstract: The objective of the paper is to answer an often-asked question : if tariff rates are reduced, what will happen to wage inequality ? We consider two types of wage inequality : between occupations (skills premium) and between industries. We use two large databases of wage inequality that have become recently available and a large data set of average tariff rates all covering the period between 1980 and 2000. We find that tariff reduction is associated with higher inter-occupational and inter-industry inequality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 30 publications
(29 reference statements)
1
41
0
1
Order By: Relevance
“…Milanovic (2002) found a more complex relationship whereby openness in low-income countries tended to benefit only the rich, but openness in higher-income countries benefited the poor and middle class to a larger degree. Looking specifically at tariffs, Milanovic and Squire (2005) found that more liberal policies were associated with increased inequality in poorer countries, but with decreased inequality in richer countries.…”
Section: Literature Concerning Determinants Of Income Inequalitymentioning
confidence: 99%
“…Milanovic (2002) found a more complex relationship whereby openness in low-income countries tended to benefit only the rich, but openness in higher-income countries benefited the poor and middle class to a larger degree. Looking specifically at tariffs, Milanovic and Squire (2005) found that more liberal policies were associated with increased inequality in poorer countries, but with decreased inequality in richer countries.…”
Section: Literature Concerning Determinants Of Income Inequalitymentioning
confidence: 99%
“…Zhu and Trefler (2005) showed that the technological catch-up that they measure with labor productivity (without linking it to imports) does not increase directly wage inequality but allows developing countries to be specialized in more skill-intensive products in their exports which, in turns, leads to an indirect increase in wage inequalities. 4 The recent study from Milanovic and Squire (2005) also use an inter-industry wage dispersion dataset. This approach allows using a larger sample since those data are easier to collect.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…We choose to use an inter-industry wage dispersion dataset, as in Milanovic and Squire (2005), so we focus on sector-based wage inequalities. We consider this approach to be adequate since clustering industries by their intensity in skilled labor enables us to identify those sectors that experience increase in wages relatively to the other sectors.…”
Section: South-south Trade and Wage Inequality: A Framework Of Analysismentioning
confidence: 99%
“…Dinopoulos and Segerstrom (1999) interpret γ as a wage dispersion parameter, with higher γ associated with larger percentage differences between the wages of highest and lowest paid skilled workers (see footnote 13 in Dinopoulos and Segerstrom, 1999). Empirical evidence (see Milanovic and Squire, 2005;Fernàndez et al, 2005;Szekely and Hilgert, 2000;Bils and Klenow, 2000) shows that wage dispersion is higher in developing countries than in developed ones. In this framework, where ability is uniformly distributed, developing countries also have larger residual wage inequality, i.e.…”
Section: Manufacturingmentioning
confidence: 99%